The Relationship between the Socio-economic Status and the Pregnancy Outcomes in the Philippines: A Systematic Review - Gutierrez, Maria Angelika; Arellano, Mariah Franchezcka; Bote, Janine; Guzman, Josephine De; Santos, Michaella; Hagosojos, Bernardino (Asian Journal of Biological and Life Sciences)
Aim/Background: Pregnancy is a remarkable preparation; however, it acquires challenges to the socio-economic status of pregnant women. This paper aims to determine if socio-economic status impacts pregnancy outcomes. Materials and Methods: The authors utilized PubMed and Google Scholar to conduct a systematic search with a language and date constraint of publications published between 2017 and 2022 and written in English. Three independent reviewers looked over the titles, abstracts, and the full content for eligibility criteria and PRISMA compliance. Results and Conclusion: Of the 1,049 articles that were searched, 7 of which were chosen and reviewed. The findings showed the association between the socio-economic status of pregnant women and the outcome of delivery. Low-income class pregnant individuals are concerned with low educational attainment, unemployment, and poverty, while the high-income class benefits more in prenatal care than the low-income class. Pregnant women, especially those in low socio-economic class, struggle the most in their everyday lives. Therefore, the causal correlation between the status of the mother and child is recommended to further elaborate on the origin of infant problems such as malnourishment and being underweight.
Keywords: Pregnancy in the Philippines; Pregnancy outcomes; Pregnant Women; Socio-economic status